Matching risk vulnerabilities with capacities for building supply chain resilience – a theoretical framework for low-probability, high-impact risks. (16th June 2022) - Zhou, Ming; Zhou, Shu; Shi, Tianqin; Park, Taeho
COVID-19 best reminds us of how every pain that is felt by supply chains goes to impact production. An aggregated framework of supply chain risk analysis is needed. This research endeavoured to theoretically structure the inter-relationships among supply chain vulnerabilities as well as corresponding capacity factors to mitigate supply chain risks and sustain supply chain resilience. An inter-relationship structure among risk vulnerabilities was mapped. Capacity factors were matched with each vulnerability category using anecdotal evidence found from various news and literature databases relevant to supply chain resilience concepts. The derived capacity-vulnerability typology revealed links between vulnerability and capacity factors and a structural model for risk prioritisation in managing low-probability, high-impact risks (LPHIRs). Production businesses and professionals shall find our findings a focused guideline for efficiently and effectively building risk resilient capacities. An extensive empirical study of our model with more comprehensive databases will better validate our theoretical results.